Oxford guide to British and American culture for learners of English (Oxford University Press, 2005)
This is the most up-to-date Guide to British and American culture that gives you an insight into what's important in both countries today, what's popular, and what people feel strongly about. It's written for learners of English, in language that's easy to understand. 10,000 entries, hundreds of illustrations including colour photos and maps, and special entries with extra vocabulary on topics such as advertising, football and soap operas all help you learn much more about both cultures.